Primary retention of permanent lower first molar: case report and twelve-year follow-up (Research, Society and Development, 2021)
Impaction of permanent first and second molars is an uncommon condition, with a prevalence rate of 0.01% to 0.08% and few cases are described in the literature. Many etiological factors are reported for failure in the eruption of these teeth. However, the mechanisms responsible for this occurrence are still unknown. This article describes the treatment of a 12-year-old patient with a permanent lower molar impacted with twelve-year follow-up. The presence of the impacted tooth was diagnosed from an asymptomatic extra-oral volumetric increase at the base of the patient's jaw. The first impacted molar was surgically removed by intraoral access under local anesthesia. The patient was not able to follow orthodontic follow-up. In 12-year follow-up, it was observed that the removal of the impacted tooth was the best option for the case. This article also offers a discussion to broaden the understanding of the causes and treatment options in cases of permanent molar impacted.